The Impact Of Customer Satisfaction On Customer Loyalty Of BCA Mobile Banking - Nur lelasari; Innocentius Bernarto (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
In order to meet the demands of customers who seek quick, simple, and affordable services, including banking services, businesses must adapt their methods of operation to the rapid growth of information and communication technology. This study seeks to ascertain what variables may directly affect customer loyalty in the usage of BCA mobile banking in Indonesia for millennials, as well as what factors can directly influence customer satisfaction to develop customer loyalty. Purposive sampling was used in this study's quantitative methodology, with a total sample size of 605, which was then analyzed using PLS-SEM. The results of the study stated that convenience had the greatest influence on increasing customer satisfaction. While the cost factor has no effect on increasing customer satisfaction in the use of BCA mobile banking, and responsive factor only has an effect on increasing satisfaction but does not affect customer loyalty. This provides benefits for developing BCA mobile banking.